Varieties of capitalism, governance and government spending: A cross-section analysis - Joachim Ahrens; Rainer Schweickert; Juliane Zenker (Kiel Institute for the World Economy (IfW), 2011)
We argue that the literature on government size suffers from neglecting the role of governance both as a driving and a limiting factor for government spending. Cross-country evidence for a sample of 126 developed and developing countries averaging data for the period 2003-07 reveals that better governance allows for higher spending. However, on the demand side, more open countries are likely to spend more in cases of minor quality of governance only. In this respect, government spending compensates ineffective institutional structures. More generally, a preference for a coordinated (continental European type) market economy leads to higher levels of spending if accompanied by better governance. While most developing countries share these preferences, Latin American countries seem to prefer a lower level of spending as in liberal (anglo-saxon) market economies.
Keywords: H10; P10; P51; 330; Government Size; Governance; Varieties of Capitalism; OECD; Developing Countries; Öffentliche Ausgaben; Staatsquote; Governance-Ansatz; Varieties of Capitalism; OECD-Staaten; Entwicklungsländer